2021
DOI: 10.1177/17479541211047661
|View full text |Cite
|
Sign up to set email alerts
|

The rugby tug-of-war: Exploring concussion-related behavioural intentions and behaviours in youth community rugby union in New Zealand

Abstract: Rugby union is a popular team sport, with a high rate of concussions. In adolescents, concussions are further complicated by issues of under-reporting. To encourage more responsible concussion behaviours, it is imperative to understand the factors that influence youth players’ behaviours, including the attitudes and behaviours of their coaches and parents. The aim of this study was to explore concussion-related behavioural intentions and behaviours that may influence effective concussion management across a yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…8,13 Thus it is critical to identify the factors, such as concussion attitudes, that facilitate reporting intention. Findings within the broader NZR concussion project 29 and in previous studies have shown that although players may understand the seriousness of concussions and the role they play in their management, conflicting attitudes (e.g., not wanting to let the team down, pressure to win) or contextual factors can negatively impact safe concussion management behaviours. 14,32 Attempting to change these attitudes with a one-off education intervention is challenging.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…8,13 Thus it is critical to identify the factors, such as concussion attitudes, that facilitate reporting intention. Findings within the broader NZR concussion project 29 and in previous studies have shown that although players may understand the seriousness of concussions and the role they play in their management, conflicting attitudes (e.g., not wanting to let the team down, pressure to win) or contextual factors can negatively impact safe concussion management behaviours. 14,32 Attempting to change these attitudes with a one-off education intervention is challenging.…”
Section: Discussionmentioning
confidence: 94%
“…Details of the focus group data collection are described previously. 29 Briefly, an interview guide was developed which included questions about roles and responsibilities, concussion education, concussion baseline assessments, and concussion management. Focus groups were facilitated by four trained interviewers experienced in qualitative methods.…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous research in Australian community rugby specifically identified confusion around real-world, ‘on-the-ground’ concussion management responsibilities as an important challenge 11 14. Examining these concussion management responsibilities in the NZR community rugby system as a collective may lead to a greater understanding of potential gaps in concussion management and facilitate the development of strategies to fill these gaps 18 21. Therefore, this study explored key stakeholder groups within the NZ community rugby system’s perceptions of their own and others’ concussion-related responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Although resources such as the International Consensus Statement on Concussion in Sport and World Rugby’s community concussion guidelines are available, stakeholder attitudes and behaviours regarding the identification and treatment of concussions lack consistency 17–20. Previous research in Australian community rugby specifically identified confusion around real-world, ‘on-the-ground’ concussion management responsibilities as an important challenge 11 14.…”
Section: Introductionmentioning
confidence: 99%
“…1 Soccer does not involve full-contact as rugby but both engage in physical contact regarded as fair charging for the ball in a distance. [2][3][4] To attain favorable performance outcomes, rugby and soccer players should possess adequate physical fitness collectively and individual skills. 5,6 Globally, emphasis is placed on the overall physical fitness parameters of rugby players such as muscular strength, muscular endurance, power, agility and flexibility either in a match or training session.…”
Section: Introductionmentioning
confidence: 99%